Biomechanical effects of body weight support with a novel robotic walker for over-ground gait rehabilitation - Mun, Kyung-Ryoul; Lim, Su Bin; Guo, Zhao; Yu, Haoyong (SPRINGER HEIDELBERG, 2017)
Body weight support (BWS) promotes better functional outcomes for neurologically challenged patients. Despite the established effectiveness of BWS in gait rehabilitation, the findings on biomechanical effects of BWS training still remain contradictory. Therefore, the aim of this study is to comprehensively investigate the effects of BWS. Using a newly developed robotic walker which can facilitate pelvic motions with an active BWS unit, we compared gait parameters of ten healthy subjects during a 10-m walk with incremental levels of body weight unloading, ranging from 0 to 40 % at 10 % intervals. Significant changes in joint angles and gait temporospatial parameters were observed. In addition, the results of an EMG signal study showed that the intensity of muscle activation was significantly reduced with increasing BWS levels. The reduction was found at the ankle, knee, and hip joints in the sagittal plane as well as at the hip joint in the frontal plane. The results of this study provide an important indication of increased lateral body balance and greater stabilization in sagittal and frontal plane during gait. Our findings provide a better understanding of the biomechanical effects of BWS during gait, which will help guide the gait rehabilitation strategies.
Keywords: WALKING SPEED; TREADMILL WALKING; JOINT MOMENTS; STROKE; KINEMATICS; INTENSITY; RESPONSES; PATTERNS; CHILDREN; DISEASE